The relationship between systemic disorders and anatomical outcomes after Descemet membrane endothelial keratoplasty - Topcu,Husna (2022)
ABSTRACT Purpose: The aim of this study was to investigate the association of anatomical outcomes and medications of patients with systemic diseases who underwent Descemet membrane endothelial keratoplasty with donor factors. Methods: Sixty nondiabetic donors of endothelial grafts and 60 patients who underwent operation by a single surgeon were included in this retrospective study. The patients’ data, including the presence of diabetes mellitus and hypertension, antidiabetic-antihypertensive medications, and intracameral tamponades and anatomical outcomes, were recorded. The donor data were obtained from eye bank records. Results: Eighteen patients had type 2 diabetes mellitus (30%) and 34 had hypertension (56.6%). Among the patients with diabetes mellitus, 13 were receiving a single-agent antidiabetic drug, 4 were receiving dual oral antidiabetic therapy, and 1 was receiving insulin therapy. Among the hypertensive patients, 11 had monotherapy and 23 had dual antihypertensive therapy. Postoperatively, 35 patients (58.3%) had an endothelial attachment, 8 (13.3%) received reinjection, 7 (11.7%) required re-Descemet membrane endothelial keratoplasty, and 10 (16.7%) underwent penetrating keratoplasty. The mean donor age was 51.2 ± 14.1 years. The most common cause of donor death was cardiopulmonary arrest (36/60 cases; 60.0%). Regression analysis revealed that the presence of diabetes mellitus significantly disrupted graft attachment (p=0.034), while the presence of hypertension, antidiabetic and antihypertensive medication use, and the type of tamponade used in the patients, and the age, sex, cause of death, and specular endothelial cell count of donors were not statistically significantly associated with graft attachment (p>0.05). Conclusion: In this study, the anatomical outcomes of Descemet membrane endothelial keratoplasty surgery were affected by recipient and donor factors. The presence of diabetes mellitus in the recipient significantly negatively affected graft attachment.